Torturous etiquettes film performance and social form - Varndell, Daniel, 1983- (SUNY series, horizons of cinema., 2023)
Explores the ""torture"" of mannered behavior and the prevalence of etiquette as a theme in classical and contemporary Hollywood and European cinema.